Sensitivity of Injection Characteristics to the Nozzle Hole Angle of a GDI Injector: A CFD Analysis - Li, Xinhai; Shang, Xianshang; Wang, Lu; Cheng, Yong (Frontiers in Energy Research, 2022)
The increase in injection pressure makes it more challenging to accurately control the injection quantity of the injector of a gasoline direct injection (GDI), thus necessitating the optimization of the parameters of the nozzle holes and the clarification of such parameters in terms of their influence on the injection characteristics, so as to improve the injector’s consistency of injection characteristics. This article adopts the computational fluid dynamics (CFD) approach to investigate the influence of nozzle angle on the gas-liquid flow, cavitation state, and fuel injection rate in the hole. The results show that when the angle of concentric holes of the nozzle exceeds 65° and keeps rising further, it will lead to the gradual decrease of the injection rate during the stable period and the continuous rise of the sensitivity to the nozzle angle. The rising injection pressure would increase the sensitivity of the injection characteristics to the angle of the concentric holes, with the strongest level of sensitivity ranging between 70° and 75°. The negative pressure area on the upper inner wall of the hole would increase with the accretion of the hole angle. As the negative eccentricity rises, the injection rate would gradually drop in both the transition period and the stable period. In contrast, the increase of positive eccentricity would lead to the gradient escalation of the injection rate in the stable period. The impact of negative eccentricity is greater than that of positive eccentricity, implying that it is necessary to reduce the deviation of negative eccentricity as much as possible during the machining and positioning process so as to ensure positioning accuracy.